The Effect of Virtual Reality on Isometric Muscle Strength - Dolu, Umut; Camliguney, Asiye Filiz (Progress in Nutrition, 2022)
The aim of the study is to determine the acute effects of virtual reality on isometric muscle strength, pain intensity, perceived exertion, and heart rate. The study sample comprised 46 male sedentary individuals with a mean age of 28,56±5,25, who don’t have a sports experience and any health problems. Participants were divided into two groups, A and B, and grouped randomly. The mean age of group A is 29,00±6,13 years, height 170,78±7,51 cm, body weight 70,58±9,57 kg. The mean age of group B is 27,69±3,94 years, height 172,69±6,32 cm, body weight 69,57±8,65 kg. During the Wall Squat Test, the participants verbally informed the perceived pain intensity and perceived exertion level every 30 seconds, and the heart rate was monitored using a smartwatch. After the first measurements were completed, a break was given for one week, and then a cross matching was made. According to the results of the study; It was determined that groups using virtual reality were more advantageous after first measurement and cross matching. Group virtual reality performed higher during the Wall Squat Test, and it was also determined that the pain intensity and perceived exertion levels were lower during the test. However, there was no significant difference in heart rate between the groups.